THE EFFECTIVENESS OF LINK SYSTEM IN TEACHING SPEAKING AT SMA YADIKA BATURAJA - Yunda Lestari (ELTE Journal (English Languange Teaching and Education), 2015)
Abstract: This study was aimed at whether link system significantly effective in teaching speaking to the eleventh grade students of SMA Yadika Baturaja. This study used pre-experimental method by taking one class as the sample of the study. The population of this study was all of the eleventh grade students of SMA Yadika Baturaja with the total number were 212 students in academic year 2013/2014 and the sample was 35 students in one class which are chosen by using purposive sampling. The data obtained through the oral test and was analyzed by using paired sample t-test of SPSS 16 program. The result of the study showed that the average students’ scores in post-test (62.16) was higher than the average students’ scores in pre-test(55.39). The result of the data analyzed through SPSS 16 program was 5.477 to tobtained  and 2. 032 to ttable with the significance level (α = 0,05) and degree of freedom (df = 35 – 1 = 34). This study showed that the alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected which means it was significantly effective to teach speaking by using link system to the eleventh grade students of SMA Yadika Baturaja. Key words: Effectiveness, Mnemonic, Link System